The influence of fraud hexagon on indication fraud - Bancin, Nova Enda Sari; Baihaqi, Baihaqi (Enrichment : Journal of Management, 2023)
This research aims to obtain test results from the influence of fraud hexagon (pressure, opportunity, rationalization, capability, arrogance and collusion) on indications of fraud. This research is a type of quantitative research and the resources used are primary data by distributing questionnaires. This research was conducted at the Local Government Organization (OPD) registered on the website of the Central Bengkulu district government. The questionnaire was distributed to employees working in the asset sector, budget field, and treasury and accounting fields as well as the general section, resulting in 65 respondents. This study used multiple linear regression analysis techniques, t tests, and coefficients of determination which were processed using the SPSS application. The results showed that the variables pressure, opportunity, capability had a positive effect on the indication of fraud. While the variables of rationalization, arrogance, and collusion do not affect the indications of fraud.